Effect of hIL10 Naked DNA Delivery on Swine Heart Tissue after Acute Infarct - Sendra, Luis; Herrero, Maria Jose; Olivera, Gladys; Diaz, Ana; Noguera, Imma; Ruiz-Sauri, Amparo; Fernandez-Delgado, Rafael; Bodí, Vicent; Alino, Salvador F (Archives of Clinical and Medical Case Reports, 2019)
Purpose: Myocardial infarct mediates an inflammatory response whose intensity limits the recovery of the damaged tissue and its function. In the present work, we evaluate the efficacy of immunomodulatory hIL10 gene hydrofection on acute myocardial infarct in pig. Methods: Pigs recently infarcted by right coronary artery block were injected with 50 ml saline solution containing the naked gene at 2 or 7 ml/s through coronary sinus. Blood samples were collected from coronary sinus before gene injection, 2 and 72 hours later for protein quantification. Heart tissue samples from normal and infarcted tissue were collected 72 hours post-transfection to evaluate the efficiency of gene delivery and decoding The results: hIL10 protein translation yielded more than 200 protein molecules/cell in normal tissue and was always higher than in infarcted areas. Coronary sinus plasma concentration of hIL10 protein reached 50 pg/ml as average. The histopathological evaluation of peri-infarct and infarct areas showed that interleukin 10 hydrofection mediated anti-inflammatory effects, as evidenced by reduced edema and cell infiltration. Conclusions: Heart hydrofection of hIL10 gene in infarct-induced pigs mediates local expression of cytokine in normal and infarcted tissue, resulting in reduced acute response triggered by the ischemic episode induced experimentally.